Популярные оперные арии: для голоса и фортепиано - Э. Направник (Тенор, 1998)
Экземпляры: ИСК (20130318) / Инвентарный номер: 1090550 / Сис.шифр: 85.943-07 / Авт.знак: П 58 / ГРНТИ: 18.41 / ББК: 85.943-07